2010
DOI: 10.1007/s11426-010-4081-1
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt, a reactive metal in releasing hydrogen from sodium borohydride by hydrolysis: A short review and a research perspective

Abstract: 1) According to the definition given by the U.S. Department of Energy, a gravimetric hydrogen storage capacity (GHSC) is the capacity of the storage system taken as a whole (i.e. hydride, tank, valves, pipes and so on). It is different from the gravimetric hydrogen density (HD) of a hydride as it takes into account the H content only. Hence, the HD cannot be directly compared to the GHSC.2) One might assume that the hydride weight represents about 50 % of the weight of the filled storage system.Cobalt is commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 66 publications
(97 reference statements)
0
28
0
Order By: Relevance
“…are found to be the most effective catalysts towards NaBH 4 hydrolysis but their high cost limits their wider use [7,8]. Cobalt-based catalysts, especially cobalt boride alloy (Co-B), have potential catalytic activity to replace noble metals in NaBH 4 hydrolysis [9,10]. Co-B catalysts can easily be synthesized by reduction of cobalt(II) salts but it has been observed that formed Co-B particles always prefer to be in agglomerated state due to high surface energy involved in the exothermic reduction process [11].…”
Section: Introductionmentioning
confidence: 99%
“…are found to be the most effective catalysts towards NaBH 4 hydrolysis but their high cost limits their wider use [7,8]. Cobalt-based catalysts, especially cobalt boride alloy (Co-B), have potential catalytic activity to replace noble metals in NaBH 4 hydrolysis [9,10]. Co-B catalysts can easily be synthesized by reduction of cobalt(II) salts but it has been observed that formed Co-B particles always prefer to be in agglomerated state due to high surface energy involved in the exothermic reduction process [11].…”
Section: Introductionmentioning
confidence: 99%
“…12 min and is due to the formation of active a Co x B phase from the Co 3 O 4 ; the second phase shows a fast growth of HGR, due to the catalytic activity of the Co x B phase, which reaches a maximum and, finally, during a third period a decrease of HGR is observed due to the depletion of the SBH in the solution. It has also been proposed that in this third phase, the alkaline pH due to the formation of sodium borate, can also lead to the oxidization of the catalyst Co x B to hydrated cobalt hydroxide species [10,18,56,57]. This would justify why the induction period remains in the following cycles.…”
mentioning
confidence: 99%
“…Despite being prepared and used in a good number of papers, the exact nature of these nanoalloys is still under intense discussion [9][10][11]18]. Co(BO 2 ) 2 is surrounding all the structure which tends to decrease in thickness and coverage degree with Ru content.…”
Section: -Introductionmentioning
confidence: 99%
“…Most proposed systems for hydrogen generation through (1) are based on the addition of stabilized (on sodium hydroxide) SB solutions to a certain catalyst or by addition of water to a mixture of solid SB and catalyst. [4][5][6]8] Cobalt is definitely the most studied metal catalyst because of its cost effectiveness [9][10][11]. Co based catalysts have been tested and/or prepared in a wide of range of forms, from the simplest CoCl 2 6H 2 O salt to metallic cobalt, cobalt oxides and also alloyed with another elements [12][13][14][15][16][17].…”
mentioning
confidence: 99%
See 1 more Smart Citation